A model for calculating the mechanical demands of overground running - Mark Waldron (Sports Biomechanics, 2020)
An energy-based approach to quantifying the mechanical demands of overground, constant velocity and/or intermittent running patterns is presented. Total mechanical work done (Wtotal) is determined from the sum of the four sub components: work done to accelerate the centre of mass horizontally (Whor), vertically (Wvert), to overcome air resistance (Wair) and to swing the limbs (Wlimbs). These components are determined from established relationships between running velocity and running kinematics; and the application of work-energy theorem. The model was applied to constant velocity running (2–9 m/s), a hard acceleration event and a hard deceleration event. The estimated Wtotal and each sub component were presented as mechanical demand (work per unit distance) and power (work per unit time), for each running pattern. The analyses demonstrate the model is able to produce estimates that: 1) are principally determined by the absolute running velocity and/or acceleration; and 2) can be attributed to different mechanical demands given the nature of the running bout. Notably, the proposed model is responsive to varied running patterns, producing data that are consistent with established human locomotion theory; demonstrating sound construct validity. Notwithstanding several assumptions, the model may be applied to quantify overground running demands on flat surfaces.